Amylo-AFFECT-QOL, a self-reported questionnaire to assess health-related quality of life and to determine the prognosis in cardiac amyloidosis - Kharoubi, Mounira; Bézard, Mélanie; Broussier, Amaury; Galat, Arnault; Gounot, Romain; Poullot, Elsa; Molinier-Frenkel, Valérie; Fanen, Pascale; Funalot, Benoit; Itti, Emmanuel; Lemonnier, François; Sing Chadha, Gagan Deep; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background and aims Self-reported questionnaires are useful for estimating the health-related quality of life (HR-QoL), impact of interventions, and prognosis. To our knowledge, no HR-QoL questionnaire has been developed for cardiac amyloidosis (CA). This study aimed to validate Amylo-AFFECT-QOL questionnaire to assess HR-QoL and its prognostic value in CA. Methods A self-reported questionnaire, “Amylo-AFFECT” had been designed and validated for CA symptoms evaluation and screening by physicians. It was adapted here to assess HR-QoL (Amylo-AFFECT-QOL) and its prognostic value in CA. To validate the theoretical model, internal consistency and convergent validity were assessed, particularly correlations between Amylo-AFFECT-QOL and the HR-QoL Minnesota Living Heart Failure (MLHF) questionnaire. Results Amylo-AFFECT-QOL was completed by 515 patients, 425 of whom (82.5%) had CA. Wild-type and hereditary transthyretin amyloidosis (ATTRwt and ATTRv) and immunoglobulin light-chain amyloidosis (AL) were diagnosed in 47.8, 14.7, and 18.8% of cases, respectively. The best HR-QoL evaluation was obtained with five dimensions: “Heart failure,” “Vascular dysautonomia,” “Neuropathy,” “Ear, gastrointestinal, and urinary dysautonomia,” and “Skin or mucosal involvement.” The global Amylo-AFFECT-QOL and MLHF scores showed significant positive correlations (rs = 0.72, p < 0.05). Patients with a final diagnosis of CA had a global Amylo-AFFECT-QOL score significantly higher than the control group composed by patients with other diagnoses (22.2 ± 13.6 vs. 16.2 ± 13.8, respectively, p-value < 0.01). According to the Amylo-AFFECT-QOL global results, ATTRv patients’ QoL was more affected than AL patients’ QoL or ATTRwt patients’ QoL. Patients with a higher HR-QoL score had a greater risk of death or heart transplant after 1 year of follow-up (log-rank < 0.01). Conclusion Amylo-AFFECT-QOL demonstrates good psychometric properties and is useful for quantifying HR-QoL and estimating CA prognosis. Its use may help to improve overall management of patients with CA.